Strategi Edukasi "Generasi Unggul" dalam Meningkatkan Karakter Kepemimpinan, Budaya Akademik, dan Komitmen Mewujudkan Lingkungan Belajar Aman pada Peserta Masa Pengenalan Lingkungan Sekolah (MPLS) - ali hanafiah; Ervita Nindy Oktoriani; Dyah Rangga Puspita (JOURNAL AKSES STIA MALANG, 2026)
The Student Orientation Program (MPLS) serves as a strategic opportunity to foster students' character as theybegin their educational journey. However, its implementation often focuses primarily on introducing the physicalschool environment, with limited emphasis on developing leadership character, academic culture, and students'commitment to creating a safe learning environment. This study aimed to analyze the effectiveness of the"Generasi Unggul" (Excellent Generation) educational program in improving leadership character, academicculture, and commitment to a safe learning environment among participants of the Student Orientation Programat SMA Negeri 1 Tumpang. A quantitative approach with a Pre-Experimental One Group Pretest–PosttestDesign was employed. The study population consisted of 420 students, with 205 respondents selected using simplerandom sampling. Data were collected using a validated and reliable questionnaire. Data analysis includeddescriptive statistics, normality testing, Paired Sample t-test, Normalized Gain (N-Gain), and Effect Size(Cohen's d) using IBM SPSS Statistics version 26. The findings revealed that the "Generasi Unggul" educationalprogram significantly improved students' leadership character, academic culture, and commitment to creating asafe learning environment (p < 0.001). The N-Gain values indicated moderate improvement in leadership character (0.62) and academic culture (0.58), while commitment to a safe learning environment showed a highlevel of improvement (0.70). The effect size analysis demonstrated large to very large effects across all variables.These findings indicate that the "Generasi Unggul" educational program is effective as a character-building modelfor student orientation activities and has the potential to be implemented as a sustainable character developmentprogram in schools